Environmental Consciousness in Hindu Tradition – A Cultural and Philosophical Perspective: हिंदू परंपरा में पर्यावरण चेतना- एक सांस्कृतिक और दार्शनिक दृष्टिकोण - Poonam; Kumar, Pintu (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
The Hindu tradition embodies a deep-rooted environmental consciousness that integrates cultural, spiritual, and philosophical values. Nature is revered not just as a life-support system but as a divine manifestation. This perspective, sustained from the Vedic era to modern times, emphasizes harmony with nature through the worship of the five elements—earth, water, fire, air, and space—collectively known as the Panchmahabhutas. Ancient scriptures like the Vedas, Upanishads, and Puranas convey messages of ecological balance, portraying Earth as a mother and nature as sacred. Practices such as tree worship, water conservation, and animal protection are central to religious rituals and festivals. Symbols and deities in Hinduism also reflect ecological wisdom, promoting a lifestyle of coexistence. In today’s era of environmental crises, this traditional ecological knowledge offers sustainable models rooted in ethics and spirituality. It advocates a shift from exploitation to reverence for nature, aligning development with dharma (righteous duty). Abstract in Hindi Language: हिंदू परंपरा में पर्यावरण चेतना गहराई से समाई हुई है, जो सांस्कृतिक, आध्यात्मिक और दार्शनिक मूल्यों से जुड़ी हुई है। प्रकृति को केवल जीवन सहायक तंत्र के रूप में नहीं, बल्कि ईश्वर के साक्षात स्वरूप के रूप में पूजनीय माना गया है। वैदिक काल से लेकर आधुनिक युग तक यह दृष्टिकोण निरंतर बना रहा है, जिसमें पंचमहाभूत—पृथ्वी, जल, अग्नि, वायु और आकाश—की आराधना के माध्यम से प्रकृति के साथ समरसता पर बल दिया गया है। वेद, उपनिषद और पुराण जैसे प्राचीन ग्रंथ पर्यावरणीय संतुलन का संदेश देते हैं, जहां पृथ्वी को मां और प्रकृति को पवित्र माना गया है। वृक्ष-पूजा, जल-संरक्षण और पशु-संरक्षण जैसे कार्य धार्मिक अनुष्ठानों और त्योहारों का अभिन्न अंग हैं। हिंदू देवी-देवताओं के प्रतीकों में भी पर्यावरणीय ज्ञान समाहित है। आज के पर्यावरण संकट के समय में यह पारंपरिक ज्ञान एक नैतिक और आध्यात्मिक आधार पर आधारित सतत जीवनशैली की दिशा में मार्गदर्शन प्रदान करता है। Keywords: लघुकथा, बिहार, हिंदी साहित्य, साहित्यिक परंपरा, समकालीन लेखन, सामाजिक संदर्भ